A new species for Limulopteryx from Cameroon with the first record of termitophilous Ptiliidae (Coleoptera) outside the Neotropics - Grebennikov, Vasily V. (Zootaxa, 2008)
A new and apparently termitophilous featherwing beetle Limulopteryx hintelmanni sp.n. from Cameroon is described and extensively illustrated. This is the first record of termitophilous Ptiliidae outside the Neotropical Region. Taxonomic position of the new species and that of the genus Limulopteryx are discussed. All records of Ptiliidae associated with termites are reviewed.